DEVELOPMENT OF FRUIT-BASED FOOD INGREDIENT FROM BUNI FRUIT (ANTIDESMA BUNIUS (L.) SPRENG.) WITH COLORING IMPACT AND ITS APPLICATIONS IN PROCESSED FOOD - Yelliantty
The manufacture of processed food requires various food ingredients to obtain the desired nutritional composition and certain technological effects. Food ingredients include all edible components required in the formulation of processed food. In Indonesia, natural food ingredients based on local raw materials have not been widely developed and produced in industrial scale. This study aims to obtain nonfood additives (FAs) natural food ingredients based on buni fruit (Antidesma bunius (L.) Spreng.) with coloring impact that can be applied for various processed foods. The research begun with determination of buni plants, followed by identification of the chemical component groups contained in buni fruit, while further identification of chemical compounds is focused on the flavonoid group. In the next stage, pulpfree buni juice was prepared and followed by the formulation of the juice into a dry buni powder with the addition of maltodextrin as an excipient using spray drying. On these preparations, various tests were carried out which included: analysis of nutritional components, colour characterization, solubility, as well as determination of heavy metal and microbiological contamination. The dried buni powder was then applied for the production of hard candy, jelly, and syrup, which represent solid, semi-solid, and liquid food products. In the final stage, organoleptic tests were carried out on each of these food products to study the effect of dried buni powder on consumer preferences. The results of the determination confirmed that the buni plant used in this study was a plant species with the scientific name Antidesma bunius (L.) Spreng. The results of the phytochemical screening showed that the buni fruit contained chemical groups of phenolic compounds, flavonoids, tannins, saponins, alkaloids, and steroids. Further identification and structural elucidation of the isolate obtained showed the presence of cilicicone A and 7-methoxy cillicicone A which are derivative of chalcone as one form of anthocyanin. Quercetin was also detected in buni fruit. The resulting dried buni powder is soluble in water and showed colour stability against light exposure in the pH of 2.72 to 7.22 and temperature of 4 to 40 ?C for14 days. Tests for heavy metal and microbial contamination showed that dry buni contained no detectable levels of Arsenic (As), Cadmium (Cd), Mercury (Hg), Lead (Pb) at each limit of detection (LOD) of 0.01, 0.01, 0.1, and 0.1 mg/kg, giving negative results for the E. coli, S. aureus, B. cereus, and Salmonella sp., as well as the total plate count (TPC) and fungi count of 2 colony/g and 1.25?10 colony/g, respectively. The colorant impact of dried buni powder in processed food products depends on the pH of the product as indicated by the ?E parameter on the chromameter. The test results showed a significant difference in the value of ?E before and after the addition of the powder. The results of organoleptic test showed that the addition of dry buni powder to the processed food samples of hard candy, jelly, and syrup was tasted by the panellists. Based on the results, it can be concluded that buni juice can be processed into food ingredients for processed foods. The stability of colour component of buni juice can be maintained and hence can be applied as an ingredient for the manufacture of processed food after formulated into dry solid. Buni fruit powder had stable colouring effect on heating under acidic and neutral pH conditions; The low temperature (4 o C) was able to maintain the colour stability of the buni fruit powder in both light and dark conditions. The preparation of food ingredients from buni fruit juice can provide an effective and stable colouring effect when applied to processed foods. The natural food ingredient based on buni fruit juice in the form of dry powder in this study is an invention. In addition, the results of the study which identified cilicicone A and 7-methoxy cilicicone A compounds can be considered as a novelty since its presence in buni fruit has not been reported in the literature. The results of this study would have a positive impact in the form of product added value and the availability of natural food ingredients based on local raw materials that meet the aspects of safety, benefit, and quality and hence can be applied for the production process of various processed foods.